1991
DOI: 10.1182/blood.v77.6.1371.bloodjournal7761371
|View full text |Cite
|
Sign up to set email alerts
|

The Senegal DNA haplotype is associated with the amelioration of anemia in African-American sickle cell anemia patients

Abstract: We have previously determined that in African sickle cell anemia (SS) patients three different beta-like globin gene cluster haplotypes are associated with different percent G gamma (one of the two types of non- alpha chains comprising hemoglobin F [HbF]), mean percent HbF, and percent dense cells. We report now that in adult New York SS patients, the presence of at least one chromosome with the Senegal haplotype is associated with higher Hb levels (1.2 g/dL higher) than is found for any other non-Senegal hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
1
13
1
1
Order By: Relevance
“…This finding is consistent with the reported influence of the Arab-Indian haplotype on HbF level [9]. Nagel et al [21] showed that the presence of only one chromosome with the Senegal haplotype, in comparison to combinations of other African haplotypes, is associated with a higher HbF level and amelioration of anemia. However, in our study population the HbF was significantly lower in the AS patient group as compared to the SS or S/thal groups by one-way ANOVA test (P < 0.001), while SS and S/thal did not have different HbF levels.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with the reported influence of the Arab-Indian haplotype on HbF level [9]. Nagel et al [21] showed that the presence of only one chromosome with the Senegal haplotype, in comparison to combinations of other African haplotypes, is associated with a higher HbF level and amelioration of anemia. However, in our study population the HbF was significantly lower in the AS patient group as compared to the SS or S/thal groups by one-way ANOVA test (P < 0.001), while SS and S/thal did not have different HbF levels.…”
Section: Discussionsupporting
confidence: 88%
“…While inexact, the proportion of African heritage by country generally correlated with prevalence of the sickle allele in newborns ( Figure 2). Older studies described the origins of the sickle cell gene through specific molecular patterns of b-globin sickle gene markers, or haplotypes [31][32][33]. The distribution of these haplotypes from Latinos with SCD originating in the U.S., Brazil, Panama, and Venezuela provide molecular data to support the African origin of the sickle gene, and demonstrate similar distributions of African regions/ethnicities of origin between sample populations tested [34][35][36][37].…”
Section: Genetic Heterogeneity Among Scd In Latin Americansmentioning
confidence: 96%
“…The Venezuelan gene pool is the product of admixture between Native Americans, European colonizers, and Africans brought as slaves mainly between 1500 and 1810 (Aizpurua, 1988). Venezuelans with an Wainscoat et al, 1983;Antonarakis et al, 1984;Hattori et al, 1986;Nagel et al, 1991;O È ner et al, 1992;Zago et al, 1992;Costa et al, 1994;Gonc Ëalves et al, 1994;Muniz et al, 1995;Pen Äaloza et al, 1995;Ke Âclard et al, 1996;Olivero, 1996;Franca et al, 1998;Pante  de Sousa et al, 1998;Bortolini and Salzano, 1999;Arends et al, 2000. important African component occupy a vast region along the Caribbean coast, from the eastern to the western part of the country (Arends, 1971;Brito Figueroa, 1983;Arends et al, 1985Arends et al, , 1990Arends et al, , 2000Castro de Guerra, 1992;Castro de Guerra et al, 1997). The presence of high frequencies of Bantu and Benin haplotypes, and in lower frequencies the Senegal haplotype, suggest that the mutation HBB*S in the Sucre and Anzoa Âtegui states is mainly of Bantu origin.…”
Section: Discussionmentioning
confidence: 99%
“…The HBS mutation (b6 Glu3 3Val) has been associated with five main haplotypes usually defined by six polymorphic restriction endonuclease sites in and around the b-like globin gene: Benin (BEN: À À À À À), Central African Republic or Bantu (CAR or BAN: À À À À À), Senegal (SEN: À À ), Cameroon (CAM: À À ) and Arab-Indian (ARB: À À), which are probably related to the clinical heterogeneity of sickle cell anemia (Nagel et al, 1987(Nagel et al, , 1991Elion et al, 1992). The presence of these haplotypes can also suggest the place of origin of mutation HBB*S in the population under study Steinberg et al, 1997;Pante de Sousa, 1999).…”
mentioning
confidence: 99%